Safety evaluation of nivolumab added concurrently to radiotherapy in a standard first line chemo-radiotherapy regimen in stage III non-small cell lung cancer—The ETOP NICOLAS trial. (July 2019) - Peters, S.; Felip, E.; Dafni, U.; Belka, C.; Guckenberger, M.; Irigoyen, A.; Nadal, E.; Becker, A.; Vees, H.; Pless, M.; Martinez-Marti, A.; Tufman, A.; et al.
Highlights: Immune- plus chemo-radiotherapy as promising strategy in curative setting of NSCLC. Concurrent PD-1/L1-inhibition and radiotherapy not yet assessed in clinical trials. Safety results of prospective trial of concurrent nivolumab and chemo-radiotherapy. No unexpected adverse events or increased risk for severe pneumonitis observed. Abstract: Objectives: Chemo-radiotherapy (CRT) and concurrent PD-1 inhibition has shown promising results in pre-clinical models. So far, the feasibility of delivering concurrent CRT and PD-1/PD-L1 inhibition has never been assessed in a clinical trial. Material and methods: NICOLAS is a phase-II trial evaluating the safety and efficacy of nivolumab combined with CRT in stage III NSCLC. Patients received 3 cycles of platinum-based chemotherapy and concurrent RT (66 Gy/33fractions). Nivolumab started concurrently with RT. The primary endpoint was 6-month post-RT rate of grade-≥3-pneumonitis. A formal interim safety analysis (IA) was scheduled when the first 21 patients reached 3 months follow-up post-RT. An early positive safety conclusion would be reached at IA if there were no grade ≥3-pneumonitis in those patients. Efficacy evaluation was planned provided the safety conclusion was reached. Results and conclusion: As of 13 December 2018, 82 patients were recruited with median follow-up of 13.4 months. The most frequent adverse events (AEs) were anaemia, fatigue and pneumonitis. No unexpected AEs or increased toxicities were observed. For the first 21 patients, no grade-≥3-pneumonitis was observed by the end of the 3-month post-RT follow-up period. The early safety IA provides evidence that the addition of nivolumab to concurrent CRT is safe and tolerable regarding the 6-month rate of pneumonitis grade ≥3 at the one-sided significance level of 5%. Following that, the 1-year progression-free survival will be evaluated in an expanded patient cohort. NICOLAS trial creates the opportunity for assessing the activity of the combination of checkpoint with concurrent CRT in larger prospective trials for locally advanced NSCLC.